Is there wisdom in a second opinion? Shadowing the ECB and the Bank of England - Matthias Neuenkirch; Pierre L. Siklos (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
The European Central Bank (ECB) and the Bank of England (BoE) are shadowed by professionals and academic economists who provide a separate policy rate recommendation in advance of the central bank's announcement. We explore differences between shadow and actual committee decisions based on an adapted Taylor role and report a few systematic differences especially in the case of euro area shadow committee when the data are disaggregated according to the background of the shadow members, and when the member's country of origin is considered.
Keywords: E52; E58; E61; E69; 330; monetary policy committees; Taylor rules; central bank communication; Geldpolitik; Gruppenentscheidung; Sachverständige; Taylor-Regel; Staatliche Information; Eurozone; Großbritannien